Children of the mist [videorecording (DVD)] - Hà, Lệ Diễm, 1991- (Film Movement, 2023)
"In a village hidden in the mist-shrouded Northwest Vietnamese mountains resides an indigenous Hmong community, home to 12-year-old Di, part of the first generation of her people with access to formal education. A free spirit Di happily recounts her experiences to Vietnamese filmmaker Diễm Hà Lệ, who planted herself within Di's family over the course of three years to document this unique coming of age. As Di grows older, her carefree childhood gives way to an impulsive and sensitive adolescence, a dangerous temperament for what will happen next; in this insular community, girls must still endure the controversial but accepted tradition of "bride kidnapping." One night, when the young girl's parents return home from celebrating the Lunar New Year, they are shocked to find their house is silent: Di has disappeared."--Container.